2018
DOI: 10.1111/jfs.12550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the spoilage potential of Shewanella putrefaciens, Aeromonas hydrophila, and Aeromonas sobria isolated from spoiled Pacific white shrimp (Litopenaeus vannamei) during cold storage

Abstract: The spoilage potential and their interactions of Shewanella putrefaciens, Aeromonas hydrophila, and Aeromonas sobria isolated from spoiled Pacific white shrimp (Litopenaeus vannamei) were evaluated by inoculation into sterile shrimp juice during 12 days at 4 °C. Based on the microbiological analysis, A. sobria was identified as non‐spoilage bacteria, and S. putrefaciens and A. hydrophila developed very rapidly as well as with a high maximum cell density in shrimp juice (up to 8.79 log cfu/g and 7.81 log cfu/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Qian et al. (2018) evaluated the spoilage potential of S. putrefaciens , Aeromonas hydrophila , and A. sobria isolated from spoiled Pacific white shrimp. The result showed that A. sobria was very weak in spoiling shrimp juice when compared with the other two bacteria.…”
Section: Relationships Between Microbiota and Quality Deterioration Omentioning
confidence: 99%
See 1 more Smart Citation
“…Qian et al. (2018) evaluated the spoilage potential of S. putrefaciens , Aeromonas hydrophila , and A. sobria isolated from spoiled Pacific white shrimp. The result showed that A. sobria was very weak in spoiling shrimp juice when compared with the other two bacteria.…”
Section: Relationships Between Microbiota and Quality Deterioration Omentioning
confidence: 99%
“…Many other reviews (Machado, Silva, Giaouris, Melo, & Simões, 2020; Odeyemi, Alegbeleye, Strateva, & Stratev, 2020) tried to elucidate microbiota composition and spoilage mechanisms in foods or foods of animal origin, whereas referring less to fishery products. Even though the relations between seafood microbiota and quality are still not comprehensively understood, there has been great interest in establishing the link between microbial activity and different quality aspects as well as on examining the spoilage potential of relevant microbes (Broekaert, K., Noseda, B., et al., 2013b; Jia, Li, et al., 2019; Liu, X., et al., 2018; Qian et al., 2018; Wang & Xie, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Shewanella putrefaciens, the Gram-negative motile bacteria belonging to the family Shewanellaceae, is a seafood spoilage organism (SSO) for cryopreserved fresh fish, that is S. putrefaciens is still a great threat to seafood even under cold storage condition [ 5 ]. This opportunistic bacteria is also associated with various clinically important infections and diseases, especially in the tropics and during summer months in temperate zones [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then the accumulation of biogenic amines was analyzed by HPLC system (SHIMADZU, LC-2010C HT, Kyoto, Japan) after filtered through a 0.45-µm membrane filter. The parameters of HPLC analysis were settled according to the method of Qian et al [28].…”
Section: Biogenic Amines Analysismentioning
confidence: 99%
“…The shrimp muscle (5 g) were m inced and stirred in phosphate buffer A (15.6 mmol/L Na 2 HPO 4 , 3.5 mmol/L KH 2 PO 4 , I = 0.05, pH 7.5, 4 • C; Sinopharm Chemical Reagent Co., Ltd., Beijing, China). The precipitate was collected after centrifugation at 1000 g and then centrifuged with phosphate buffer B (15.6 mmol/L Na 2 HPO 4 , 3.5 mmol/L KH 2 PO 4 , 0.45 mol/L KCl, I = 0.5, pH 7.5, 4 • C) at 1000 g, 4 • C. The Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE, GenScript Co., Ltd., Nanjing, China) was conducted referring to the method of Qian et al [28].…”
Section: Extraction Of Muscle Proteins and Electrophoresismentioning
confidence: 99%